2003
DOI: 10.1063/1.1566462
|View full text |Cite
|
Sign up to set email alerts
|

Mercury cadmium telluride/tellurium intergrowths in HgCdTe epilayers grown by molecular-beam epitaxy

Abstract: Surface crater defects in HgCdTe epilayers grown by molecular-beam epitaxy have been investigated using cross-sectional scanning and transmission electron microscopy, as well as atomic force microscopy. These defects originated primarily within the HgCdTe films, and were shown to be associated with the local development of polycrystalline morphology. High-resolution observations established the occurrence of finely spaced HgCdTe/Te intergrowths with either semicoherent or incoherent grain boundaries, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…10,22,23 Within a surface crater defect, crystals of both HgCdTe and Te continue to nucleate, with the HgCdTe grains being either semicoherent or incoherent to the Te grains. 10 Energy-dispersive X-ray spectroscopy (EDS) data also confirmed the existence of excessive Te in the surface crater defects (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…10,22,23 Within a surface crater defect, crystals of both HgCdTe and Te continue to nucleate, with the HgCdTe grains being either semicoherent or incoherent to the Te grains. 10 Energy-dispersive X-ray spectroscopy (EDS) data also confirmed the existence of excessive Te in the surface crater defects (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The TEM measurements have been discussed in detail elsewhere, 10,[22][23][24][25] including the additional steps required to reduce ion-milling damage and preparation artefacts. 25 …”
Section: Methodsmentioning
confidence: 99%
“…Mercury-rich MCT is widely used for the fabrication of infrared devices [5][6][7][8][9]. The cadmium-rich compound, on the other hand, has promising application in solar cells [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of HgCdTe surface crater defects was shown to be associated with the development of polycrystalline morphology, and high-resolution observations revealed finely spaced HgCdTe/Te intergrowths that had nucleated within the HgCdTe epilayers. 23 SLs of HgTe/Hg 0.05 Cd 0.95 Te grown on CdZnTe(211) substrates have also been studied, and high-resolution studies using annular dark-field (or Z-contrast) imaging revealed interdiffusion and changes in well/barrier widths as a result of low-temperature annealing. 24 …”
Section: Cdznte(211)b Substratementioning
confidence: 99%